Characterization of Laves phase in Crofer 22 H stainless steel. (July 2015) - Hsiao, Zheng-Wen; Kuhn, Bernd; Chen, Delphic; Singheiser, Lorenz; Kuo, Jui-Chao; Lin, Dong-Yih
Highlights: Morphology of Laves phase changes from strip-like to needle-shaped above 700 °C. Laves phase precipitates from grain boundaries to grain interiors above 700 °C. The grain size of ferritic matrix is independent of annealing temperature. Abstract: This study investigated the effect of annealing temperature on the precipitation behavior of Crofer ® 22 H at 600 °C, 700 °C, and 800 °C. The grain size distribution, precipitate phase identification, and microstructure were analyzed using electron backscatter diffraction (EBSD) and energy dispersive X-ray spectroscopy (EDS). The morphology of Laves phase (Fe, Cr, Si)2 (Nb, W) precipitates having the Cr2 Nb structure changed from strip-like to needle-shaped as the annealing temperature was increased. The precipitates of the Laves phase also shifted from the grain boundaries to the grain interiors when the temperature was increased. However, the average grain size (150 μm) of the ferritic matrix did not significantly change at 600 °C, 700 °C, and 800 °C for 10 h.